PERANCANGAN PUSAT KEBUGARAN DI KOTA PONTIANAK - zulfadli zulfadli; Muhammad Nurhamsyah; Irwin Irwin (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
Along with the development of the times, human life is also changing, the pattern of life and activities in every job that requires the community, especially big cities to be ready in prime condition. In carrying out daily activities, humans tend to use brain functions more than muscles, so humans are more likely to be lazy to spend more energy. This causes many people to experience obesity, stress, physically unhealthy etc. The purpose of the fitness center is to provide comfort with sports facilities provided for the community. The activities in the form of a gym, aerobics, yoga, swimming, jogging and several other sports that aim to train muscles and reduce weight, make the ideal body as desired. In planning a fitness center as a place for exercise and sports, the design must be in the form of a building with a large space. The application of green open space in the building can be applied to the garden in the building, with wide openings in each room so as to be able to take advantage of the ventilation sanded with vegetation to make the room feel comfortable and cool. This application is suitable for sports areas, because when doing sportsactivities the body requires smooth oxygen circulation. Destroyed ventilation with vegetation is also able to provide health for the body while exercising.